Experimental atopic dermatitis is dependent on the TWEAK/Fn14 signaling pathway. (17th September 2019) - Liu, Q.; Wang, H.; Wang, X.; Lu, M.; Tan, X.; Peng, L.; Tan, F.; Xiao, T.; Xiao, S.; Xia, Y.
Summary: Tumor necrosis factor (TNF)‐like weak inducer of apoptosis (TWEAK) acts through its receptor fibroblast growth factor inducible 14 (Fn14), and participates in skin inflammation. Both TWEAK and Fn14 are highly expressed in skin lesions of patients with atopic dermatitis. The purpose of this study was to further explore the effect of Fn14 inhibition on experimental atopic dermatitis. Experimental atopic dermatitis was induced in the wild‐type and Fn14 knock‐out BALB/c mice. The effect of TWEAK/Fn14 interaction on keratinocytes was studied in an in‐vitro model of atopic dermatitis. Fn14 deficiency ameliorates skin lesions in the mice model, accompanied by less infiltration of inflammatory cells and lower local levels of proinflammatory cytokines, including TWEAK, TNF‐α and interleukin (IL)‐17. Fn14 deficiency also attenuates the up‐regulation of TNFR1 in skin lesions of atopic dermatitis. Moreover, topical TWEAK exacerbates skin lesion in the wild‐type but not in the Fn14 knock‐out mice. In vitro, TWEAK enhances the expressions of IL‐17, IL‐18 and IFN‐γ in keratinocytes under atopic dermatitis‐like inflammation. These results suggest that Fn14 deficiency protects mice from experimental atopic dermatitis, involving the attenuation of inflammatory responses and keratinocyte apoptosis. In the context of atopic dermatitis‐like inflammation, TWEAK modulates keratinocytes via a TNFR1‐mediated pathway. Abstract : Fn14 deficiency significantly ameliorates atopic dermatitis‐like lesion in BALB/c mice. In skin lesion, activated TWEAK/Fn14 signals upregulate the expressions of proinflammatory cytokines, which greatly contribute to skin inflammation. Under atopic dermatitis microenvironment, the predominance of TNFR1 is associated with apoptosis of keratinocytes through the Fn14‐TRAF2‐TNFR1 axis.